2019
DOI: 10.3390/antiox8090328
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a (miR-34a) Mediates Retinal Endothelial Cell Premature Senescence through Mitochondrial Dysfunction and Loss of Antioxidant Activities

Abstract: Stress-associated premature senescence (SAPS) is involved in retinal microvascular injury and diabetic retinopathy. We have investigated the role and mode of action of miR-34a in retinal endothelial cells senescence in response to glucidic stress. Human retinal microvascular endothelial cells (HuREC) were exposed to glucidic stress (high glucose (HG) = 25 mM d-glucose) and compared to cells exposed to normal glucose (NG = 5 mM) or the osmotic control l-glucose (LG = 25 mM). HG stimulation of HuREC increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…That study suggested oxidative/nitrative stress as a cause of premature senescence in diabetic retinas. Further investigation confirmed cellular senescence in human RECs subjected to HG which was associated with increased oxidative stress and mitochondrial dysfunction [94].…”
Section: Arginase In Premature Cellular Senescencementioning
confidence: 76%
“…That study suggested oxidative/nitrative stress as a cause of premature senescence in diabetic retinas. Further investigation confirmed cellular senescence in human RECs subjected to HG which was associated with increased oxidative stress and mitochondrial dysfunction [94].…”
Section: Arginase In Premature Cellular Senescencementioning
confidence: 76%
“…Recent studies revealed that the microRNA might be an indispensable regulator (Yamakuchi and Hashiguchi, 2018). Thounaojam et al (2019) found that overexpression of miR-34a could decrease the expression of SIRT1 directly and induce mitochondrial dysfunction in high glucose-induced retinal endothelial cells. Thus, miR-155-5p, miR-106b, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous microRNAs (miR-3197, miR-2116-5p, miR-152, miR-34a, etc. ) are identified as specificity biomarkers, and they participate directly in DR progression (Fu and Ou, 2019;Ji et al, 2019;Thounaojam et al, 2019). SIRT1 is a NAD + -dependent protein deacetylase, which plays important roles in metabolic regulation and adaptation (Boutant and Cantó, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, caloric restriction presented cardioprotective effects through SIRT1/PGC-1α activation in ob/ob mice with cardiac hypertrophy [195]. Finally, a recent study into human retinal microvascular endothelial cells has demonstrated that high glucose stimulation increases miR-34a expression, which induces cellular senescence by mitochondrial dysfunction and loss of antioxidant capacity through PGC-1α deficiency [196].…”
Section: Type 2 Diabetesmentioning
confidence: 99%